Complete mitochondrial genome of the spotted alfalfa aphid, Therioaphis trifolii (Hemipera: Aphididae) - Xinzhi Liu; Shuhua Wei; Jia He; Fan Song; Hu Li; Wanzhi Cai (Mitochondrial DNA. Part B. Resources, 2019)
The complete mitochondrial genome (mitogenome) of Therioaphis trifolii is sequenced and annotated based on high-throughput sequencing method in the present study. It is a typical circular DNA molecule of 16,068 bp, with 37 genes and 82.6% A + T content. The gene order is the same as the putative ancestral arrangement of insects. Thirteen protein-coding genes (PCGs) start with an ATN codon and terminate with a TAA codon or a single T residue. All the 22 tRNAs, ranging from 64 to 73 bp, have the typical clover-leaf structure except for trnS1. The length of rrnL and rrnS genes are 1265 bp and 779 bp respectively. The control region is 856 bp in length with 85.2% A + T content. The phylogenetic tree supports the monophyly of Aphidinae and the sister relationship between T. trifolii and seven species of subfamily Aphidinae.